The Rise of India’s Soft Power in the Post-Cold War Era and Its Regional Ramifications, with an Emphasis on Pakistan - Rehman, Hafeez Ul; Warraich, Saqib Khan; Kharl, Sanwal Hussain (Annals of Human and Social Sciences, 2023)
The objective of the research is to evaluate India’s soft power initiatives on the power dynamics and geopolitical landscape of the region as a whole, including the effects on Pakistan and the region. India’s immense influence in South Asia and thriving economy make it significant in global as well as regional politics. New Delhi’s strategic, political, regional, economic, and cultural policies affect Pakistan. Military and political aspects have been extensively studied, but the rising importance of soft power makes it vital to study. The developments in communication, the internet, social media, cultural programming (arts & film), and online video streaming (soft-power instruments) have changed the battlefields. This study employs qualitative techniques. India dominates the region in diplomacy, culture, and economy. Pakistan seemed to be influenced by Indian soft power instruments. It can improve its image globally, which is influenced by Indian propaganda through political stability, economic prosperity, and public diplomacy.